Numerical Modelling of Dust Propagation in the Atmosphere of Tbilisi City: The Case of Background Eastern Fresh Breeze - Kukhalashvili, Vepkhia G.; Gigauri, Natia G.; Surmava, Aleksandre A.; Demetrashvili, Demuri I.; Intskirveli, Liana N. (Journals of Georgian Geophysical Society, 2020)
Dust propagation at Tbilisi city territory in case of strong background eastern winds is studied using the 3D regional model of atmospheric processes evolution and integration of the equation of admixtures transfer-diffusion. It is shown that dust propagation substantially depends on both the terrain of city and surrounding territories and on the magnitude and direction of background wind velocity. It is obtained that dust propagation process in case of strong background wind is characterized by time variation and spatial distribution peculiarities. High pollution zones as well as the reasons of their time variation and dust accumulation are determined. It is established that a high pollution level (1.2-2.0 MAC) is obtained in the time interval from 3 p.m. to 9 p.m. in the up to 50 m thick lower part of surface layer of the atmosphere.